Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3945/ajcn.115.115188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc supplementation on serum zinc concentration and T cell proliferation in nursing home elderly: a randomized, double-blind, placebo-controlled trial

Abstract: Background: Zinc is essential for the regulation of immune response. T cell function declines with age. Zinc supplementation has the potential to improve the serum zinc concentrations and immunity of nursing home elderly with a low serum zinc concentration. Objective: We aimed to determine the effect of supplementation with 30 mg Zn/d for 3 mo on serum zinc concentrations of zincdeficient nursing home elderly. Design: This was a randomized, double-blind, placebo-controlled study. Of 53 nursing home elderly (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 52 publications
3
70
0
4
Order By: Relevance
“…Besides vitamin D (the most important of all nutraceuticals for immune function), other vitamins that strengthen immunity include vitamin C and vitamin E (De la Fuente et al 1998;Moriguchi and Muraga 2000). Zinc (Barnett et al 2016) (80 mg/day during period of infection) and probiotics (Sharma et al 2014) have also been shown to benefit the immune system.…”
Section: Pay Attention To Physical Healthmentioning
confidence: 99%
“…Besides vitamin D (the most important of all nutraceuticals for immune function), other vitamins that strengthen immunity include vitamin C and vitamin E (De la Fuente et al 1998;Moriguchi and Muraga 2000). Zinc (Barnett et al 2016) (80 mg/day during period of infection) and probiotics (Sharma et al 2014) have also been shown to benefit the immune system.…”
Section: Pay Attention To Physical Healthmentioning
confidence: 99%
“…Zinc supplementation has a potential effect on immune function impairment caused by a decrease in serum zinc concentration due to advanced age. 40 Without affecting the normal healing process, the main challenge of stenting in the treatment of coronary heart disease is to prevent restenosis. 41 Therefore, stent design with good compatibility and prevention of intestinal stricture is critical for the treatment of intestinal stricture.…”
Section: Biocompatibility Of Intestinal Eluting Stentsmentioning
confidence: 99%
“…In innate immunity, zinc keeps the epithelial membrane of natural barrier structure and function (Hojyo and Fukada 2016). Acute zinc deficiency causes a decrease in innate immunity (Gruber and Rink 2013;Rink and Gabriel 2000), while chronic deficiency increases inflammation (Maares and Haase 2016;Barnett et al 2016).…”
Section: Trace Elementsmentioning
confidence: 99%